(untitled) (Research, Society and Development, 2022)
Introduction: Proportional mortality is considered to be the measure of the importance of a specific cause of death in relation to all causes of death in the same population group, being able to relate to sex, age group, among others. In this sense, studies based on epidemiological data allow us to investigate aspects involved about the possible causes that have caused the increasing increase in deaths. Objective: To analyze epidemiological data on proportional mortality and the transitions that occurred in the health process in the state of Alagoas during the period from 2010 to 2019. Methodology: Descriptive study, based on recorded data on proportional mortality in the State of Alagoas. All records were obtained through the DataSus platform and collected in August 2021. Results: An increase in the mortality of individuals aged over 40 years was analyzed, related to diseases of the circulatory system. High number of deaths from external causes in males in the 20-29 age group. Deaths in children under 1 year of age are related to conditions originating in the perinatal period, such as prematurity and factors related to childbirth and the postpartum period. In males, there is a higher mortality rate. Conclusion: Analyzing the causes of death over the 10 years, there is a prevalence of diseases of the circulatory system with progression over the years, while due to external causes of morbidity and mortality varied, with regression in recent years. There was also a gradual increase in mortality from neoplasms over the decade studied. Being prevalent, mortality by male sex.